GENETIC POLYMORPHISMS OF CYP11B2 GENE IN HYPERTENSION - MAZHAR, S; WAJID , A; FIRDOUS , U (Biological and Clinical Sciences Research Journal, 2024)
Hypertension is a complex, multifactorial disease influenced by both genetic and environmental factors. Essential hypertension is partially hereditary, with alterations in aldosterone synthesis and regulation potentially playing a role. Low-renin hypertension, characterized by an elevated ratio of aldosterone to plasma renin activity, is associated with inappropriate aldosterone biosynthesis. The cytochrome P450 family 11 subfamily B member 2 (CYP11B2) gene, which encodes aldosterone synthase, has been suggested as a possible candidate in the genetic predisposition to hypertension. Objective: This study aimed to investigate the association between the CYP11B2 gene polymorphism −344T/C (HaeIII) and hypertension by analyzing the allelic frequency and genotype distribution in hypertensive patients and healthy controls. Methods: A total of 65 hypertensive cases and 42 controls (including both males and females) were enrolled. Genomic DNA was extracted, and the CYP11B2 −344T/C polymorphism was analyzed using PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism). The allelic frequency and the distribution of TT, TC, and CC genotypes in both cases and controls were examined. Results: The analysis revealed that the control group exhibited a higher frequency of the TT genotype, while the patient group displayed an increased prevalence of both CT and CC genotypes. Notably, the C allele was not observed in the control samples but was present at a significantly higher frequency in hypertensive patients. Statistical analysis indicated that the C allele was a significant risk factor for hypertension (p < 0.01).Conclusion: Our findings suggest that the CYP11B2 −344T/C polymorphism may contribute to the genetic predisposition to hypertension, particularly in individuals with a family history of the disease. These results highlight the importance of genetic factors in hypertension susceptibility and underscore the need for follow-up studies to assess the long-term risk and incidence of hypertension in individuals carrying genetic risk factors.